Isiris™ for Ureteric Stent Removal in Renal Transplantation: An Initial Single-Centre Experience of 150 Cases. (June 2021) - Doherty, Daniel T.; Moinuddin, Zia; Grey, Ben R.; van Dellen, David
Background . Ureteric stent insertion is performed at the time of renal transplant to minimise the risk of post-operative urological complications, including anastomotic leak and ureteric stenosis or obstruction. Transplant ureteric stent removal (TUSR) has historically been performed via flexible cystoscopy, predominantly in a theatre setting. Isiris™ is a single-use cystoscope with integrated grasper designed for removal of ureteric stents. We report our initial experience. Methods . A retrospective analysis of a contemporaneously maintained database was performed with review of case notes from October 2017 to September 2018. TUSR was performed by surgical middle grades with a single nurse assistant. Results . One hundred and fifty ureteric stents were removed in transplant recipients (mean age 50.2 years, SD ± 15.2; 61.3% male). 91.3% ( n = 137) of cases were performed in the outpatient clinic. Median time to TUSR was 42 days (IQR 30-42). 147 attempts at removal were successful. One urinary tract infection (UTI) was reported following TUSR. Use of the Isiris™ for TUSR corresponds to a £63, 480 saving in this cohort compared to conventional practice. This value is conservative and does not include income that has been gained from the reallocation of operating theatre capacity. Conclusion . Isiris™ can safely be employed for the timely performance of non-complicated TUSR. Isiris™ releases this procedure from the confines of the operating theatre to the outpatient clinic. This reduces the resource burden for healthcare providers and may result in improved patient satisfaction. The environmental implications of disposable healthcare equipment require consideration. Evaluation of Isiris™ TUSR for encrustation is required.